2013
DOI: 10.1345/aph.1r757
|View full text |Cite
|
Sign up to set email alerts
|

Nepafenac: An Ophthalmic Nonsteroidal Antiinflammatory Drug for Pain After Cataract Surgery

Abstract: The 2 nepafenac products appear to be equally efficacious, with a slightly increased adverse event rate in patients using the 0.3% versus 0.1% formulation. Head-to-head clinical trials that compare the 0.3% product with the 0.1% product or other commercially available NSAIDs are unavailable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 23 publications
1
20
0
2
Order By: Relevance
“…Similarly, the authors who used nepafenac in photorefractive keratectomy (PRK) and cataract surgery concluded that topical nepafenac was safe and effective to perform topical analgesia. [9][10][11][12] The control of pain originating from the cornea and/or conjunctiva is a problem for the patients undergoing surgeries related to ocular surface, such as pterygium surgery, refractive surgery, and strabismus surgery. There are many techniques and methods described for the management of postoperative pain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, the authors who used nepafenac in photorefractive keratectomy (PRK) and cataract surgery concluded that topical nepafenac was safe and effective to perform topical analgesia. [9][10][11][12] The control of pain originating from the cornea and/or conjunctiva is a problem for the patients undergoing surgeries related to ocular surface, such as pterygium surgery, refractive surgery, and strabismus surgery. There are many techniques and methods described for the management of postoperative pain.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 Nepafenac (Nevanac; Alcon, Turkey) has been used to control the pain after many ocular surgeries. [9][10][11][12] It is unique among ophthalmic NSAIDs in that it is a prodrug deaminated to amfenac, a highly effective nonselective COX inhibitor. 13 It has superior corneal permeability characteristics compared with other available topical NSAIDs that minimize surface complications often observed with topical NSAIDs 14 and has been proven to have an acceptably great margin of safety.…”
mentioning
confidence: 99%
“…With the significant progress in surgical techniques and apparatus such as phacoemulsification, modern cataract surgery has achieved a reduction of physical surgical trauma and a decrease in the release of prostaglandins, which plays the main role in the progress of postoperative ocular inflammation [1, 2]. However, most patients still manifest clinically significant postoperative ocular inflammation after cataract surgery.…”
Section: Introductionmentioning
confidence: 99%
“…However, most patients still manifest clinically significant postoperative ocular inflammation after cataract surgery. Uncontrolled intraocular inflammation may disrupt the blood-ocular barrier and cause the entry of inflammatory cells and cytokines into aqueous humor, leading to patient discomfort, delayed recovery, suboptimal visual outcomes and even further complications such as cystoid macular edema (CME), synechiae formation, raised intraocular pressure (IOP), corneal edema, intraoperative miosis, hyperemia, photophobia and so on [24]. In this epoch of patients’ high expectations and premium intraocular lenses, not only suboptimal visual outcomes but also postoperative discomfort are unacceptable to most patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation